Author Correction: Large-scale targeted sequencing identifies risk genes for neurodevelopmental disorders - Wang, Tianyun; Hoekzema, Kendra; Vecchio, Davide; Wu, Huidan; Sulovari, Arvis; Coe, Bradley P; Gillentine, Madelyn A; Wilfert, Amy B; Perez-Jurado, Luis A; Kvarnung, Malin; Sleyp, Yoeri; Earl, Rachel K; et al. (Nature communications, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.